1972
DOI: 10.2134/agronj1972.00021962006400050019x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between the Content of Oil, Protein, and Sugar in Soybean Seed1

Abstract: The oligosaccharides, raffinose and stachyose, have been implicated as causative factors for the flatulence and uncomfortable feeling often experienced after consuming products containing soybean [Glycine max (L.) Merrill] meal. Soybeans are primarily grown for their oil and protein content. Their value might be enhanced, however, if the oil and protein content remained high and the oligosaccharide content were lowered to make them more acceptable for human consumption. Seeds of 60 selected lines from Maturity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
172
4
11

Year Published

1991
1991
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(230 citation statements)
references
References 2 publications
43
172
4
11
Order By: Relevance
“…A negative correlation between oil and protein contents was observed for both years. A similar negative correlation has also been reported by Hymowitz et al (1972), Liu et al (1995) and Kumar et al (2006). In this study minimum, maximum and average air temperatures during seed filling stage were higher ( Dornbos and Mullen (1992) have shown that seeds from plants exposed to 35°C during seed fill contained 4% more protein and 2.6% less oil than those exposed to 29°C.…”
Section: Discussionsupporting
confidence: 87%
“…A negative correlation between oil and protein contents was observed for both years. A similar negative correlation has also been reported by Hymowitz et al (1972), Liu et al (1995) and Kumar et al (2006). In this study minimum, maximum and average air temperatures during seed filling stage were higher ( Dornbos and Mullen (1992) have shown that seeds from plants exposed to 35°C during seed fill contained 4% more protein and 2.6% less oil than those exposed to 29°C.…”
Section: Discussionsupporting
confidence: 87%
“…Reducing sugars were extracted by the method of Hymowitz et al (23) and quantitatively determined by the colorimetric method of Dubois et al (24).…”
Section: Methodsmentioning
confidence: 99%
“…O rendimento de grãos de soja, em geral, é inversamente correlacionado com o teor de proteína nos grãos (Johnson et al, 1955;Kwon & Torrie, 1964;Byth et al, 1969aByth et al, , 1969bThorne & Fehr, 1970;Hartwig & Hinson, 1972;Hymowitz et al, 1972;Shannon et al, 1972;Voldeng et al, 1997;Wilcox & Guodong, 1997). Segundo Burton (1984), correlações negativas entre rendimento de grãos e teor de proteína, apesar de freqüentes, usualmente não são expressivas.…”
Section: Introductionunclassified
“…Os teores de proteína e de óleo são inversamente correlacionados (Johnson et al, 1955;Kwon & Torrie, 1964;Thorne & Fehr, 1970;Hymowitz et al, 1972;Simpson Junior & Wilcox, 1983;Burton, 1984).…”
Section: Introductionunclassified